Combination of the parent analogue of remdesivir (GS-441524) and molnupiravir results in a markedly potent antiviral effect in SARS-CoV-2 infected Syrian hamsters - Abdelnabi, Rana; Maes, Piet; de Jonghe, Steven; Weynand, Birgit; Neyts, Johan (Frontiers in Pharmacology, 2022)
Remdesivir was the first antiviral drug to be approved for the treatment of severe COVID-19; followed by molnupiravir (another prodrug of a nucleoside analogue) and the protease inhibitor nirmatrelvir. Combination of antiviral drugs may result in improved potency and help to avoid or delay the development of resistant variants. We set out to explore the combined antiviral potency of GS-441524 (the parent nucleoside of remdesivir) and molnupiravir against SARS-CoV-2. In SARS-CoV-2 (BA.5) infected A549-Dual™ hACE2-TMPRSS2 cells, the combination resulted in an overall additive antiviral effect with a synergism at certain concentrations. Next, the combined effect was explored in Syrian hamsters infected with SARS-CoV-2 (Beta, B.1.351); treatment was started at the time of infection and continued twice daily for four consecutive days. At day 4 post-infection, GS-441524 (50 mg/kg, oral BID) and molnupiravir (150 mg/kg, oral BID) as monotherapy reduced infectious viral loads by 0.5 and 1.6 log10, respectively, compared to the vehicle control. When GS-441524 (50 mg/kg, BID) and molnupiravir (150 mg/kg, BID) were combined, infectious virus was no longer detectable in the lungs of 7 out of 10 of the treated hamsters (4.0 log10 reduction) and titers in the other animals were reduced by ~2 log10. The combined antiviral activity of molnupiravir which acts by inducing lethal mutagenesis and GS-441524, which acts as a chain termination appears to be highly effective in reducing SARS-CoV-2 replication/infectivity. The unexpected potent antiviral effect of the combination warrants further exploration as a potential treatment for COVID-19.